Seismic Performance of the Inerter and Negative Stiffness–Based Dampers for Vibration Control of Structures - Islam, Naqeeb Ul; Jangid, R. S. (Frontiers in Built Environment, 2021)
Passive energy dissipation devices or supplemental damping devices have been successfully implemented into structures for controlling the excessive vibrations under wind and seismic excitation. Recent developments in the form of negative stiffness dampers (NSDs) and inerter-based vibration absorbers (IVAs) as potential energy dissipation devices are of considerable interest to researchers. The present study evaluates the performance of the combined NSD and IVA as a possible alternative to the traditional energy dissipation devices such as viscous dampers (VDs) and viscoelastic dampers (VEDs). The mathematical formulation and optimal design of the combined NSD and IVA mechanism are presented. A 20-storey benchmark building is modeled as a multi-degree-of-freedom (MDOF) shear building. The dynamic equations for the MDOF building are written in the state-space form, and a simple optimization approach based on effective modal damping is prescribed. Comparative performance between traditionally applied and novel IVA and NSD is investigated. The design considerations to analyze structures employing combined NSDs and IVAs are developed. It is demonstrated that NSDs and IVA-based passive energy dissipation devices are the most efficient devices in reducing inter-storey drifts and floor accelerations compared with VDs and VEDs using the same damping coefficient.